The Moderating Role of Website Familiarity in the Relationships Between e-Service Quality, e-Satisfaction and e-Loyalty - Kaya, Bahar; Behravesh, Elaheh; Abubakar, A. Mohammed; Kaya, Omer Sami; Orus, Carlos (Routledge Journals, Taylor & Francis Ltd, 2019)
Intense competition drives e-tailers to search for radically new ways to maintain and increase their market share. Drawing on Bagozzi's (1992) appraisal -> affective response -> behavior framework, this study highlights the need, and develops a framework for customer e-loyalty and website familiarity for e-tailer. The purpose of this study is to investigate the moderating role of website familiarity in the relationships between e-service quality, e-satisfaction and e-loyalty in the context of an emerging economy, Turkey. The survey data were obtained using a judgmental sampling technique and analyzed through structural equation modeling. The findings show that website familiarity has a significant positive moderating effect on the relationship between e-satisfaction and e-loyalty, while e-service quality positively affects e-loyalty directly and indirectly through e-satisfaction. Implications for research and practice are discussed.
Keywords: Customer e-satisfaction; e-loyalty; e-service quality; website familiarity